2012
DOI: 10.1097/inf.0b013e31824f34e6
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of a Single Dose of Meningococcal Group C Conjugate Vaccine Given at 3 Months of Age to Healthy Infants in the United Kingdom

Abstract: In conclusion, a single priming dose of either MCC-TT or MCC-CRM197 administered at 3 months of age can be used together with the Hib/MCC-TT booster in the second year of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…However, infants receiving MCC-CRM followed by MCC-TT had significantly reduced MenC and lower Hib antibody responses compared to all other groups and lower than those measured historically in similar UK trials [21]. In infants receiving mixed MCC vaccine schedules, TT-specific and DT-specific antibody responses were also influenced by which MCC vaccine was administered first.…”
Section: Discussionmentioning
confidence: 93%
“…However, infants receiving MCC-CRM followed by MCC-TT had significantly reduced MenC and lower Hib antibody responses compared to all other groups and lower than those measured historically in similar UK trials [21]. In infants receiving mixed MCC vaccine schedules, TT-specific and DT-specific antibody responses were also influenced by which MCC vaccine was administered first.…”
Section: Discussionmentioning
confidence: 93%
“…Off-label use of conjugate vaccines may be considered in cases when no other vaccination is available and protection against meningococcal disease is indicated (see below). Recently it has been shown that one single dose of monovalent MCC vaccination is sufficiently immunogenic in more than 95% of children at 3 months of age [62]. Further data are necessary to assess protective immunogenicity of tetravalent conjugate vaccines in the youngest age groups.…”
Section: Available Vaccinesmentioning
confidence: 98%
“…Over the following months, a decline in both groups was observed followed by an increase post booster, with similar proportions in both groups. This trial did not include a control group of those vaccinated with 2 doses in infancy, however comparison of the GMTs obtained in the trial of Findlow et al 14 to those of Southern et al, 13 show that the reduction of the number of priming doses from 2 to one does not impact on the magnitude of the SBA GMT prior to boosting or that following Menitorix boosting.…”
Section: Evidence Supporting a Single Infant Priming Dosementioning
confidence: 99%
“…These data led to the exploration of a single dose of MCC at 3 months of age, which is thought to be an immunologically less demanding age. 14 UK infants were immunised at 3 months of age with NeisVac-C Ò or Menjugate Ò along with concomitant Pediacel Ò (Sanofi Pasteur) and 7-valent pneumococcal conjugate vaccine (Prevenar, Pfizer). Results of this trial showed at one month following the priming dose (at 4 months of age) the SBA GMT was significantly higher in the group who received NeisVac-C Ò , with GMTs of 95.8 (66.4-138.2) in those vaccinated with Menjugate Ò compared to 223.3 (162.9-306.1) following NeisVac-C Ò vaccination.…”
Section: Evidence Supporting a Single Infant Priming Dosementioning
confidence: 99%